Urbanization and it’s effect towards community lifestyle: A case study at Melaka Tengah / Nurul Azmiyah Shuhadak and Nur Hanisah Anis Ahmad - Shuhadak, Nurul Azmiyah; Ahmad, Nur Hanisah Anis (Faculty of Administrative Science and Policy Studies, 2013)
Urbanization process has been grown in Malaysia since the early of independence which is from 1957. This process of urbanization has give effects to communities’ lifestyle especially urban dwellers. The indicator of this study is the effect of urbanization towards the communities lifestyle includes the dependence on convenience living, squatter settlements and less social interaction. Descriptive and inferential statistics were used in order to analyze the variables in this study. Analysis is based on primary data that is the survey questionnaires. The result from the analysis shows that, the communities in Melaka Tengah understand the process of urbanization. Urbanization also makes the rise of squatter settlement and dependence on convenience living. However, despite the rapid growth of urbanization, the social interaction of the communities in Melaka Tengah does not affected as they still interact with each other unlike in other urban cities where they are supposed to have lesser social interaction with each other.